Lithofacies Paleogeography and Geological Survey of Shale Gas - Mou, Chuanlong; Wang, Xiuping; Wang, Qiyu; Ge, Xiangying; Zan, Bowen; Zhou, Kenken; Chen, Xiaowei; Liang, Wei (The China Geological Survey Series, 2023)
This is an open access book. This book presents new theory and methods on compiling lithofacies paleogeographic maps as a key tool for guiding geological survey on shale gas. The fundamental goal of the shale gas geological survey is to find the 'dessert' area. It is therefore suggested that the lithofacies paleogeographic study and the technique of mapping should be a solid scientific basis for shale gas exploration. It takes Ordovician Wufeng-Silurian Longmaxi Formation in Sichuan Basin and its adjacent area as an example to illustrate how to find the 'dessert' area of shale gas in geological survey phase by compiling lithofacies paleogeographic map. It's a valuable reference for both scientific research and teaching courses in the fields of sedimentary lithofacies, paleogeography, stratigraphy, and oil and gas.